Psoralidin inhibits osteosarcoma growth and metastasis by downregulating ITGB1 expression via the FAK and PI3K/Akt signaling pathways - Shengwen Cheng; Senrui Liu; Bowen Chen; Chengcheng Du; Pengcheng Xiao; Xuefeng Luo; Li Wei; Yiting Lei; Chen Zhao; Wei Huang (BMC, 2023)
Abstract Background Psoralea corylifolia is a medicinal leguminous plant that has long been used to treat various diseases. Psoralidin (PSO) is the main extract compound of P. corylifolia and exhibits antibacterial, antitumor, anti-inflammatory, antioxidant, and other pharmacological activities. PSO has demonstrated inhibitory effects in several cancers; however, its inhibitory effect on osteosarcoma has not been reported. This study aimed to evaluate the inhibitory effect of PSO on osteosarcoma and elucidate the underlying molecular mechanisms. Methods Crystal violet, cell counting kit-8 (CCK8), and 5-Ethynyl-2'-deoxyuridine (EdU) staining assays were used to assess the inhibitory effect of PSO on the proliferation of 143B and MG63 osteosarcoma cells. Wound healing and Transwell assays were conducted to evaluate the effects of PSO on osteosarcoma cell migration and invasion. The cell cycle and apoptosis were analyzed using flow cytometry. To determine the possible molecular mechanisms, RNA-sequencing was performed and protein expression was analyzed by western blotting. The inhibitory effect of PSO on osteosarcoma in vivo was analyzed using a mouse model of orthotopic osteosarcoma and immunohistochemistry. Results PSO inhibited osteosarcoma cell proliferation in a concentration-dependent manner, inhibited cell migration and invasion, and induced cell-cycle arrest and apoptosis. Mechanistically, PSO treatment significantly inhibited the focal adhesion kinase (FAK) and phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways by downregulating ITGB1 expression in both MG63 and 143B cells. Furthermore, we demonstrated that PSO restrained osteosarcoma growth in vivo. Conclusion PSO may suppress osteosarcoma via the FAK and PI3K/Akt signaling pathways by downregulating ITGB1 expression.